Measuring the olfactory bulb input-output transformation reveals a contribution to the perception of odorant concentration invariance - Storace, Douglas A.; Cohen, Lawrence B. (Nature Publishing Group, 2017)
Humans and other animals can recognize an odorant as the same over a range of odorant concentrations. It remains unclear whether the olfactory bulb, the brain structure that mediates the first stage of olfactory information processing, participates in generating this perceptual concentration invariance. Olfactory bulb glomeruli are regions of neuropil that contain input and output processes: olfactory receptor neuron nerve terminals (input) and mitral/tufted cell apical dendrites (output). Differences between the input and output of a brain region define the function(s) carried out by that region. Here we compare the activity signals from the input and output across a range of odorant concentrations. The output maps maintain a relatively stable representation of odor identity over the tested concentration range, even though the input maps and signals change markedly. These results provide direct evidence that the mammalian olfactory bulb likely participates in generating the perception of concentration invariance of odor quality.